2021
DOI: 10.1101/2021.05.07.443200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA toxicity and perturbation ofrRNA processing in spinocerebellar ataxia type 2

Abstract: BACKGROUND: Spinocerebellar ataxia type 2 (SCA2) is a neurodegenerative disease caused by expansion of a CAG repeat in Ataxin-2 (ATXN2) gene. The mutant ATXN2 protein with a polyglutamine tract is known to be toxic and contributes to the SCA2 pathogenesis. OBJECTIVE: Here we tested the hypothesis that the mutant ATXN2 transcript with an expanded CAG repeat (expATXN2) is also toxic and contributes to SCA2 pathogenesis. METHODS: The toxic effect of expATXN2 transcripts on SK-N-MC neuroblastoma cells and primary … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…18,19 This study opens up lines of investigation into the possible role of ribosomal abnormalities in another neurodegenerative disorder. 20 Taken together, the report by Li et al, 9 along with their earlier finding of a toxic antisense ATXN2 transcript, presents evidence for combinatorial protein-RNA driven pathology in SCA2 (Fig. 1).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…18,19 This study opens up lines of investigation into the possible role of ribosomal abnormalities in another neurodegenerative disorder. 20 Taken together, the report by Li et al, 9 along with their earlier finding of a toxic antisense ATXN2 transcript, presents evidence for combinatorial protein-RNA driven pathology in SCA2 (Fig. 1).…”
supporting
confidence: 55%
“…[3][4][5][6] SCA2 belongs to a growing class of nucleotide repeat expansion disorders arising from unstable repeats in the genome. 7,8 In this issue of Movement Disorders, Li et al 9 add to an expanding body of literature indicating that repeat expansion disorders are often characterized by plural molecular pathogenic mechanisms.…”
mentioning
confidence: 99%
“…RNA-mediated toxicity may arise from aberrant interactions between mutant RNA and its protein partners in specific cell compartments. Several studies have demonstrated that mutant CAG mRNAs sequester proteins, including MBNL1, SRSF6, U2AF65, and nucleolin, alter key cellular mechanisms including alternative splicing regulation, ribosomal RNA maturation, recruitment of translation factors, and deregulation of the microRNA machinery [ 22 , 61 , 62 , 63 ]. Undoubtedly, any alteration in the aforementioned processes could impact on Müller cells’ function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mutant RNA aggregates have been detected in fibroblasts from patients with these polyQ disorders [ 20 ]. In SCA3, the expression of untranslated CAG repeats in Drosophila caused the loss of neuronal integrity in the nervous system and the eye [ 21 ], while in SCA2, the abnormal interactions between mutant CAG transcript and RNA binding proteins resulted in neurotoxicity and deregulation of ribosomal RNA maturation [ 22 ]. Finally, the HD mutant RNA was found to provoke either defective alternative splicing, deregulated microRNA (miRNA) expression, or altered translation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the expanded ATXN2 transcript aberrantly interacts with the transducin β-like protein 3 (TBL3), an RBP that is required for rRNA processing. The consequent failure of rRNA maturation could prevent the assembly of ribosomal proteins into ribosomal ribonucleoprotein subunits, hence contributing to neuronal death [108].…”
Section: Rna-mediated Toxicitymentioning
confidence: 99%